ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SESUDAH PENGADOPSIAN EMPLOYEE STOCK OPTION PROGRAM - Septarina, Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to find out the comparison of company financial performance which consists of financialratios such as net profit margin, return on assets, return on equity, and total assets turnover before and afteradopting Employee Stock Option Program (ESOP). The samples are taken by using purposive sampling methodand as many as 10 companies are selected by the researcher. The descriptive analysis technique is applied in thisresearch as the data analysis technique. The analysis is conducted by comparing the company financialperformance 1 year before and after the adoption of ESOP. The result indicates the 1 year period of companyfinancial performance after the adoption of ESOP which consists of financial ratios i.e. net profit margin, returnon assets,andreturn on equity are undergoing decreasing, while financial ratio of total assets turnover isundergoing increasing when it is compared to the 1 year period company financial performance before theadoption of ESOP. The comparison result of 1 year period of company financial performance before and 2 yearsafter the adoption of ESOP is similar to the comparison result of 1 year period of company financial performancebefore and 1 year after the adoption of ESOP.Keywords: Employee Stock Option Program(ESOP), Financial Performance, Financial Ratio